2004
DOI: 10.1080/09637480400002966
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of 8-year-old rural and urban Italian children: a study in Pistoia, Tuscany

Abstract: In this study, performed in the province of Pistoia (Italy), we tested whether 8-year-old children living in rural areas differed from their urban peers as far as nutritional status, dietary habits and physical activity are concerned. The study sample was randomly selected to include 50% of the children attending the third elementary class in the province of Pistoia during 2002. A total of 1006 children underwent an anthropometric evaluation and an assessment of dietary habits and physical activity by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
5
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 12 publications
5
19
5
3
Order By: Relevance
“…Interestingly, overweight and risk of overweight were more frequent among Russians than among Kazakhs and male urban children were at greater risk than their rural peers. This is in contrast with the finding that in Western countries, where overweight is presently more frequent among rural than among urban children (Caballero, 2005;Gracey, 2003;McMurray et al, 1999;Tognarelli et al, 2004). However, before 1980, urban areas were at greater risk of overweight than rural areas (Dietz and Gortmaker, 1984;Malina, 1993) and the same phenomenon is currently observed for some developing countries (Jackson et al, 2003;Pena Reyes et al, 2003).…”
Section: Overweightcontrasting
confidence: 84%
“…Interestingly, overweight and risk of overweight were more frequent among Russians than among Kazakhs and male urban children were at greater risk than their rural peers. This is in contrast with the finding that in Western countries, where overweight is presently more frequent among rural than among urban children (Caballero, 2005;Gracey, 2003;McMurray et al, 1999;Tognarelli et al, 2004). However, before 1980, urban areas were at greater risk of overweight than rural areas (Dietz and Gortmaker, 1984;Malina, 1993) and the same phenomenon is currently observed for some developing countries (Jackson et al, 2003;Pena Reyes et al, 2003).…”
Section: Overweightcontrasting
confidence: 84%
“…Even though similar studies, which compare dietary habits of children by the environment of living, are scarce, the results from other studies seem to agree with ours. In a recent study in Italy, which has many common elements in food culture with Cyprus, showed complete similarity of dietary habits between 927 eight-year-old, rural and urban children 25 . Two studies from Greece, (a country with which Cyprus shares a very similar food culture), concluded that differences regarding diet composition of rural and urban children either do not exist 26 , or there are minor differences that do not even follow a consistent pattern 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Σε ότι αφορά όμως την επίδραση του τόπου διαμονής στη σωματική δραστηριότητα, στη σωματική επάρκεια και στην αναπνευστική λειτουργία παιδιών, τα αποτελέσματα των μέχρι τώρα μελετών είναι αντικρουόμενα. Συγκεκριμένα, σχετικά με την επίδραση του τόπου διαμονής στα επίπεδα σωματικής δραστηριότητας των παιδιών, κάποιες μελέτες βρήκαν υπεροχή των παιδιών από αστικές περιοχές (Kristjansdottir & Vilhjalmsson, 2001;Parks, Housemann, & Brownson, 2003;Taks et al, 1991;Wilcox, Castro Housemann, & Brownson, 2000), άλλες βρήκαν υπεροχή των παιδιών από μη αστικές περιοχές (Carroll, Hostetter, & Eastman, 1996;Dollman et al, 2002;Eastman, Hostetter, & Carroll, 1992;Kabagambe, Baylin, Siles, & Campos, 2002;Ozdirenc, Ozcan, Akin, & Gelecek, 2005;Proctor et al, 1996), ενώ υπάρχουν και μελέτες που δεν έχουν βρει διαφορές μεταξύ παιδιών από αστικές και μη αστικές περιοχές (Booth, Okely, Chey, Bauman, & Macaskill, 2002;McMurray, Harrell, Bangdiwala, & Deng, 1999;Tognarelli et al, 2004). Επίσης, σχετικά με την επίδραση του τόπου διαμονής στα επίπεδα σωματικής επάρκειας των παιδιών, κάποιες μελέτες βρήκαν υπεροχή των παιδιών από αστικές περιοχές (McMurray, Harrell, Bangdiwala, & Gangsky, 1995;McNaughton, Morgan, Smith, & Hannan, 1996;Sunnegardh, Bratteby, & Sjodin, 1985;Wolanski, 1985), άλλες βρήκαν υπεροχή των παιδιών από μη αστικές περιοχές (Corlett & Mokgwathi, 1987;Ewing, Watkins, & Farrally, 1982;Watkins, Farrally, & Ewing, 1981;Wilczewski, Sklad, Krawczyk, Saczuk, & Majle, 1996), ενώ υπάρχουν και μελέτες που δεν έχουν βρει διαφορές μεταξύ παιδιών από αστικές και μη αστικές περιοχές (Booth, Okely et al, 1999;Krombholz, 1997).…”
Section: εισαγωγηunclassified
“…Συγκεκριμένα, οι Yogi et al, (1976) (Kristjansdottir & Vilhjalmsson, 2001;Parks et al, 2003;Taks et al, 1991;Wilcox et al, 2000). Από την άλλη, υπάρχουν άλλες μελέτες που είτε αναφέρουν αντίθετα αποτελέσματα (Carroll et al, 1996;Dollman et al, 2002;Eastman et al, 1992;Kabagambe et al, 2002;Ozdirenc et al, 2005;Proctor et al, 1996;Raudsepp & Pall, 1999;Sobngwi et al, 2002), είτε δεν βρίσκουν διαφορές μεταξύ αστικών και μη αστικών περιοχών (Booth et al, 2002;McMurray et al, 1999;Tognarelli et al, 2004). Στην υπεροχή των μη αστικών περιοχών αναφορικά με τη συμμετοχή σε φυσικές δραστηριότητες συνηγορεί μια σειρά μελετών.…”
Section: τόπος διαμονής και βιολογική ωρίμανσηunclassified
See 1 more Smart Citation